Rancang Bangun Sistem Komunikasi Data Pemesanan pada Drive Thru Toko Roti ETU Polinema Berbasis Android - Dwika Rahman Irianto; Moh. Abdullah Anshori; Putri Elfa Mas’udi (Jurnal Jaringan Telekomunikasi, 2020)
The rapid development of technology increases the competitive power of the business world which is getting bigger. This technology has information and communication systems that are easily accessible by the internet. In a restaurant / shop has different ordering systems. Drive thru is a service that is considered a modern system, consumers can easily order food or drinks even though they are still in the vehicle and do not need to enter the store. In the drive thru ordering system, consumers come to the intended shop and can order food from the vehicle without the need to enter the restaurant, where the order is ordered directly in front of the microphone outlet which is connected to the cashier specifically for drive thru consumers and if so, consumers can continue. to the cashier to make payments and take orders. In this study, a food ordering system is proposed for the drive thru store, by making an application and web admin where consumers can place orders quickly, and there is also Qrcode which functions as a sign of user purchases and Epay's balance which simplifies the payment process. Web functions as admin data. The test results can be concluded that the Qrcode detection on Qrcode scanner has an average reading accuracy at a distance of 2.98cm, in the Qos test which is carried out with different networks, the result is that the Telkomsel provider gets the smallest delay with a value of 0.121766.